A Survey on The Acceptance of Non-Nutritive Sweeteners among Hospitalised Diabetic Patients - Abdul Jalil, Nur Wadhihah; Rusali, Roszanadia; Osman, Noor Suzana; Wan Mahmood, Wan Fathin Fariza (International Journal of Allied Health Sciences, 2025)
Background: The prevalence of Type 2 Diabetes Mellitus (T2DM) in Malaysia continues to rise, largely due to excessive sugar consumption. Non-nutritive sweeteners (NNS), such as stevia and erythritol, are increasingly used as alternatives due to their low caloric content and minimal impact on blood glucose. However, the acceptance of NNS among diabetic patients remains uncertain. This study aimed to assess the acceptance of a stevia-erythritol blend among hospitalised diabetic patients. Methods: A cross-sectional sensory evaluation was conducted among 69 T2DM patients hospitalised at one of the teaching hospital in east coast MalaysiaParticipants consumed tea sweetened with a stevia-erythritol blend and rated its sweetness, aftertaste, and overall acceptability using a 5-point hedonic scale. Demographic data, body mass index (BMI), blood glucose levels, and length of hospital stay were also recorded. Results: Most of participants (66.7%) accepted the NNS-sweetened tea. Mean scores indicated positive responses for sweetness (3.71 ± 0.86), aftertaste (3.70 ± 0.85), and overall acceptability (3.86 ± 0.91). Conclusion: The findings indicate that diabetic patients generally accepted NNS, with sensory attributes such as sweetness and aftertaste playing a key role in their acceptance. These results support the inclusion of more palatable NNS-based options in hospital food services to promote better dietary adherence and glycaemic control in T2DM management.